The effectiveness of the educational robot in developing the creative thinking skills of the ninth-grade students in the Sultanate of Oman - Al-Mujaini, Abdullah Hammad Humaid (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to determine the effectiveness of the educational robot in developing creative thinking skills among the ninth-grade students in the Sultanate of Oman. The (ADDIE) model for educational design to build experimental materials for the study related to the educational robot, and the creative thinking scale was applied before and after the study sample. creativity among the ninth-grade students in the Sultanate of Oman according to the ratio (Mac Gojian ≥ 0.06), where the calculated ratio was (1.13), Considering this, the researcher presented a set of recommendations and proposals for implementation in the educational field with regard to the educational robot and creative thinking, methods and methods of teaching it in schools.